"And now for the good news…" the impact of negative and positive messages in self-management education for people with Type 2 diabetes: A qualitative study in an ethnically diverse population. (March 2016) - Eborall, Helen C; Virdee, Satnam K; Patel, Naina; Redwood, Sabi; Greenfield, Sheila M; Stone, Margaret A
Objectives: To explore the impact of Diabetes Education and Self Management for Ongoing and Newly Diagnosed (DESMOND) Foundation education, particularly from interviewees' narratives regarding recall of good and bad news messages and behaviour changes. Methods: In-depth, semi-structured interviews were conducted with a purposive sample (n=19) of people who had attended education sessions as part of a randomised controlled trial in two UK sites with ethnically diverse populations. Data collection and analysis were informed by the constant comparative approach and facilitated through charting. Results: Findings were similar in people from different ethnic backgrounds. Exploration of levels of recall of the sessions suggested that this was variable and sometimes very limited, but that interviewees had all assimilated some relevant learning. Key themes emerged relating to the way in which interviewees recalled and had been influenced by positive (good news) and negative (bad news) messages within the education sessions, including biomedical explanations. Both types of message appeared to have an important role in terms of motivation to change behaviour, but a notable observation was that none of the interviewees recalled receiving bad news messages when diagnosed. Discussion: Our findings have highlighted the importance of providing and combining both negative and positive messages within education designed to promote self-management behaviour change.